Carotid endarterectomy using regional anesthesia: technique and considerations - Padmanaban, Varun; Caldwell, Catherine; Milne, Indigo; Hazard, Sprague W.; Harbaugh, Robert E.; Church, Ephraim W. (Frontiers in Surgery, 2024)
Background Carotid endarterectomy (CEA) is one of the most effective operations in minimizing stroke risk in both symptomatic and asymptomatic patients with carotid stenosis in the United States. Awake CEA with regional anesthesia may decrease both perioperative complications and length of hospital stay. Techniques of performing awake CEA is not often described in published literature. Objective To describe our experience with CEA using regional anesthesia with a focus on patient selection, anatomic variations, and surgical technique including cervical regional block. We particularly focus on nuances of the awake approach. Methods CEA using regional anesthesia is described in detail. Results Successful use of regional anesthesia during CEA without complication. Conclusion Regional anesthesia for CEA is an advantageous approach for cervical plaque removal in appropriate patients. Thoughtful patient selection, as well as understanding of anatomy and its variants, is required. Potential advantages and disadvantages are discussed.